Relationship Of Lay People's Characteristics To Knowledge Of Basic Life Support Measures In Liliba Village, Kupang City - Aty, Yoany Maria Vianney B.; Alexander, Rizky; Gonsalves, Dominggos; Onggang, Fransiskus (Poltekkes Kemenkes Banjarmasin, 2023)
Heartdisease is one of the emergency conditions that can be life-threatening and result in death if not treated immediately. Cases of cardiac arrest are a cause of death that often occurs in the community, both in developed and developing countries. It is very important for ordinary people to know the first handlers in cardiac arrest cases, so that unwanted things do not happen, such as disability or even death. An important determinant in the survival of cardiac arrest victims is the cardiopulmonary resuscitation action. Objective know the relationship of the characteristics of the lay community with knowledge of basic life support measures in liliba sub-district of Kupang city Types of quantitative research descriptive design. The populationof RT 015 RW 15 Liliba Village, Oebobo District, Kupang City is 141 people. Thesample was 59 people. The instrument used in the questionnaire consists of 20 questions. Knowledge scoring is good if the score is 76-10 0, sufficient if the score is 56-75- and is scored less if thescore is < 56. Data collection was carried out by distributing questionnaires to respondents during August 2022. Descriptive data analysis and Chi Square test to obtain the relationship of respondent characteristics with knowledge of Basic Life Support. The results showed that people's knowledge about BHD was mostly good. There is a relationship between education level and knowledge of BHD with a p value of 0.042. Knowledge about BHD is very important to be known by ordinary people, in order to be able to do early assistance so that it can provide life expectancy to cardiac arrest sufferers